APPLICATION OF CHARACTER EDUCATION IN THE SCHOOL CULTURE AT 14 BANDA ACEH STATE ELEMENTARY SCHOOL - Laura Oktaviany Marantika; Siti Mayang Sari; Sariakin Sariakin (Sensei International Journal of Education and Linguistic, 2024)
The purpose of this study was to determine the application and evaluation of character education values in school culture at public elementary school 14 banda aceh. This research used a qualitative approach with a descriptive research type. Data analysis was carried out through data reduction and data collection and conclusion drawing/verification. The results showed that character education in the culture of public primary school 14 banda aceh is implemented in the layers of artifacts and values and beliefs. The planning consists of determining character values, namely religion, discipline, environmental care, national spirit, and respect for achievement; program preparation; policy socialization; and condition planning. The implementation is through the provision of facilities for various programs designed to shape student character through habituation activities. In general, SD negeri 14 banda aceh has achieved school success indicators in the implementation of the four main character values and the value of environmental care which is the focus of implementation. Evaluation is carried out through monitoring and evaluation at the end of the semester with the instrument of violation records and monitoring observation results. The aspects of evaluation include planning, completeness of facilities, implementation, achievement of targets and comparison of conditions.